Criteria and Methods for Selecting a Project in a Project Portfolio in Modern Business Conditions - Angelova, Antoaneta (Research Papers, 2017)
In recent years, understanding the role of project management in achieving the organization's strategic goals has increased significantly. This role is key in terms of the growth potential of the organization and the strengthening of its competitive position. In the spirit of this challenge, in modern times, methods of managing the project portfolio are increasingly used. This paper aims to present the conducted empirical study among experts in the field of project management. The study elements are techniques, methods and criteria for selecting a project in a project portfolio. An original questionnaire is developed and the methodology of the expert assessment is applied, summarizing the opinions of practitioners in this field. One of the main tasks of the project is the presentation of the basic concepts related to the nature of the project portfolio, project portfolio management and selection of project in the project portfolio. There is a different set of project selection tools and methods and a set of appropriate criteria that would be useful for the project selection process in a project portfolio. An analysis of the results obtained is carried out and the possibilities of project selection in project portfolio in the contemporary business conditions are presented. Limitations: the sample is on principle “respondents”.
Keywords: Project management; Project portfolio; Selection of project; Project selection methods; Project selection criteria; Expert evaluation